Efficient Generation of Megakaryocytes From Human Induced Pluripotent Stem Cells Using Food and Drug Administration-Approved Pharmacological Reagents. (23rd February 2015) - Liu, Yanfeng; Wang, Ying; Gao, Yongxing; Forbes, Jessica A.; Qayyum, Rehan; Becker, Lewis; Cheng, Linzhao; Wang, Zack Z.
Abstract : An efficient system was developed to generate megakaryocytes (MKs) from human induced pluripotent stem cells (hiPSCs) under a feeder-free and xeno-free condition, in which all animal-derived products were eliminated. Additional maturation and investigation of hiPSC-derived MKs should provide insights into MK biology and lead to the generation of large numbers of platelets ex vivo. Abstract: Megakaryocytes (MKs) are rare hematopoietic cells in the adult bone marrow and produce platelets that are critical to vascular hemostasis and wound healing. Ex vivo generation of MKs from human induced pluripotent stem cells (hiPSCs) provides a renewable cell source of platelets for treating thrombocytopenic patients and allows a better understanding of MK/platelet biology. The key requirements in this approach include developing a robust and consistent method to produce functional progeny cells, such as MKs from hiPSCs, and minimizing the risk and variation from the animal-derived products in cell cultures. In this study, we developed an efficient system to generate MKs from hiPSCs under a feeder-free and xeno-free condition, in which all animal-derived products were eliminated. Several crucial reagents were evaluated and replaced with Food and Drug Administration-approved pharmacological reagents, including romiplostim (Nplate, a thrombopoietin analog), oprelvekin (recombinant interleukin-11), and Plasbumin (human albumin). We used this method to induce MK generation from hiPSCs derived from 23 individuals in two steps: generation of CD34 + CD45 + hematopoietic progenitor cells (HPCs) for 14 days; and generation and expansion of CD41 + CD42a + MKs from HPCs for an additional 5 days. After 19 days, we observed abundant CD41 + CD42a + MKs that also expressed the MK markers CD42b and CD61 and displayed polyploidy (≥16% of derived cells with DNA contents >4N). Transcriptome analysis by RNA sequencing revealed that megakaryocytic-related genes were highly expressed. Additional maturation and investigation of hiPSC-derived MKs should provide insights into MK biology and lead to the generation of large numbers of platelets ex vivo.